A Review Article: Fall Incidents and Interior Architecture— Influence of Executive Function in Normal Ageing - Chanbenjapipu , Phumdecha; Chuangchai, Warawoot; Thepmalee , Chutamas; Wonghempoom , Apiruck (Journal of Architectural/Planning Research and Studies (JARS), 2022)
Many ageing people are staying at home, whether they are self-isolating or social distancing, because of the current Covid-19 situation. Fall incidents at home among the ageing are significantly associated with a high level of mortality. Bathrooms are frequently reported as a major environmental hazard in connection with falls. This serious health risk raises the matter of interior architecture. In terms of preventing falls, more architectural research focuses on interior elements e.g., handrail design, and non-slip mat, whilst less attention is paid to the issue of how ageing causes falls. Therefore, this article sheds light on the normal ageing process through an executive function that helps in the fall prevention of ageing people via decision-making and problem-solving. Normal ageing gradually results in declining executive function, including cognitive and motor functions, which limits and reduces day to day activities. The cognitive function (as a system) involves processing speed, accuracy in response, and error response whereas the motor function (as a mechanism) defines both gross and fine motor functions. A combination of cognitive and motor functions reflects conditions that may lead to a fall. Regarding the executive function, interior architecture for preventing falls in normal ageing people is strongly encouraged e.g., clear layout, timesaving activity, simplicity of design, lighting uniformity, short walking distance, cased opening, lightweight fixtures, and fine texture flooring. This article reviews the literature to address the knowledge gaps between interior architecture and human-centred design through ageing ergonomics, and employs a behaviour-focused aspect to interpret results for interior architects. Electronic databases, including Scopus, PubMed, and Google Scholar, were searched to specify appropriate papers, which were restricted to those in the English language. To improve the quality of the elderly’s life, this article provides recommendations that could assist interior architects in this challenge.